2014
DOI: 10.1016/j.biopsych.2013.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Sensitivity to the Depressive-like Effects of the Kappa Opioid Receptor Agonist U-50488 in Rats

Abstract: Background Dynorphin, an endogenous ligand at kappa opioid receptors (KOR), produces depressive-like effects and contributes to addictive behavior in male non-human primates and rodents. Although comorbidity of depression and addiction is greater in women than men, the role of KORs in female motivated behavior is unknown. Methods In adult Sprague Dawley rats, we used intracranial self-stimulation (ICSS) to measure effects of the KOR agonist (±)-trans-U-50488 methanesulfonate salt (U-50488) (0.0 – 10.0 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 88 publications
12
92
2
Order By: Relevance
“…Some data also suggest that morphine serves as a stronger reinforcer in females than males in self-administration procedures (Cicero et al, 2003). Similar to these effects with morphine, the kappa opioid agonist U50,488 was also more potent to depress ICSS in male rats than in females responding under a frequency-rate procedure (Russell et al, 2013).…”
Section: A Statesmentioning
confidence: 87%
See 3 more Smart Citations
“…Some data also suggest that morphine serves as a stronger reinforcer in females than males in self-administration procedures (Cicero et al, 2003). Similar to these effects with morphine, the kappa opioid agonist U50,488 was also more potent to depress ICSS in male rats than in females responding under a frequency-rate procedure (Russell et al, 2013).…”
Section: A Statesmentioning
confidence: 87%
“…Rates of drug abuse are higher in males than females (SAMHSA, 2012), and efforts have been made to examine sex differences in drug effects on ICSS. Males and females do not differ with regard to baseline sensitivity to the reinforcing effects of electrical stimulation of the MFB, and sensitivity in females is also stable across stages of the estrous cycle (Stratmann and Craft, 1997;Russell et al, 2013). However, exogenously administered estradiol facilitates ICSS in ovariectomized female rats (Galankin et al, 2010) and exogenous testosterone facilitates ICSS in castrated male rats (Olds, 1958a).…”
Section: A Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Female C57BL/6 mice (60-90 days old; Charles River Laboratories, Raleigh, NC), and homozygous KOR knockout (KO) mice and wild-type (WT) littermate mice (120-180 days old, shipped from the Scripps Research Institute, La Jolla, CA) were used for this study. We exclusively used female mice, as it has been reported that female animals showed a greater or selective sensitivity to KORmediated behaviors such as antinociception, motivation, mood-related disorders, and social interaction (Chang et al, 2000;Chakrabarti et al, 2010;Lawson et al, 2010;Liu et al, 2011;Robles et al, 2014;Russell et al, 2014). The genetic background of KOR KO and WT mice was a hybrid C57BL/6Orl  129/SV strain.…”
Section: Methodsmentioning
confidence: 99%